The Success of Currency Reforms to End Great Inflations: An Empirical Analysis of 34 High Inflations - Peter Bernholz; Peter Kugler (University of Basel, Center of Business and Economics (WWZ), 2007)
The estimation of an ordered probit model for currency reforms trying to end 31 hyperinflations and three big inflations of the 20th century shows that the introduction of an independent central bank and the adoption of a credibly fixed exchange rate are crucial for the success of a currency reform. In addition, currency reforms are demonstrated to be more difficult in centrally planned economies than in market economies.
Keywords: E31; E58; E65; 330; Great inflations; currency reforms; central bank independence; fixed exchange rate; Hyperinflation; Währungsreform; Zentralbankunabhängigkeit; Fester Wechselkurs; Wirkungsanalyse; Probit-Modell; Schätzung; Welt